MAPPING SCHOOL INCLUSION: OPERATIONALIZATION OF THE INDIVIDUALIZED EDUCATIONAL PLAN (IEP) FOR CHILDREN WITH AUTISM (Interdisciplinary Studies Journal, 2025)
This article aims to investigate the efficiency of a pedagogical record for children with autism in Early Childhood Education, for the operationalization of the Individualized Educational Plan (IEP). For this, qualitative case study research was used, in which the research subject was a 3-year-old boy diagnosed with Autism Spectrum Disorder (ASD). The pilot proposal originated within the scope of doctoral research, based on the theoretical assumptions of the Zone of Proximal Development (ZPD) (Vygotsky), Meaningful Learning (Ausubel) and SOLO Taxonomy (Biggs). After collecting and analyzing the data, the learner's information was organized into a virtual spreadsheet called REI - Individualized Educational Repository. The results showed that the pedagogical record has the function of compiling information about skills and competencies developed by the learner contemplating an IEP, with the aim of mapping the development of learning, operationalizing the necessary curricular adaptations. It is concluded that the panoramic and systematized view of skills and competencies developed during the learner's school career is fundamental for the operationalization of the PEI, in order to include the monitoring of the significant teaching and learning process, in the short, medium and long term.
Keywords: Autism Spectrum Disorder (ASD); Learning monitoring; Individualized educational repository; Meaningful Learning; Pedagogical Record